The satire of Thomas Peacock ("Crotchet Castle") - Chekalov, Ivan (Literatūra, 1973)
Thomas Love Peacock’s novels are marked with the specific blend of wit, humour and satire. They belong to what J. B. Priestley calls "novels of talk", or "novels of opinion". It is not through the plot or even characters themselves but through the whimsical confrontation of opinions that the reader’s interest is sustained. As a novelist Peacock may be linked to Carlyle, Meredith, and Butler. The article deals with "The Crotchet Castle". The very title of the novel points to the whimsicality of the author’s intentions. The opinions voiced by the characters are arranged with such clever constructional subtlety that it is not always easy to say what the author is driving at. The conflict of opinions is centred round the juxtaposition of romantic transcendentalism, on the one hand, and utilitarianism, on the other. The author presents the exponents of either doctrine as sheer crotcheteers. So both transcendentalism and utilitarianism are satirized. But the sting of Peacock’s satire is somewhat softened. His aim is not so much castigation as slyness. The fanciful arrangement of sly witticisms plentifully coined in the novel betrays, on the author’s part, a good-natured smile of self-resignation. In this respect Peacock follows the tradition of Sterne. Good-natured hedonistic humour is at the core of the author’s stylistic evaluation.